The Effect of School Leadership, Achievement Motivation on the Performance of Teachers of SMPN at Paguyaman District of Boalemo Regency - Dewa Ayu Gina Priyanti; Yosep P. Koton; William I. S. Mooduto (Jurnal Ilmu Manajemen dan Bisnis, 2021)
The objectives of this study were 1) to find out that there was a direct influence of the principal's leadership on the performance of SMP Se Paguyaman teachers; 2) knowing that there is a direct effect of achievement motivation on the performance of junior high school teachers in Paguyaman District, 3) knowing that there is a direct influence of the principal's leadership and achievement motivation on the performance of SMP Se Paguyaman teachers. The quantitative descriptive research method approach with the type of survey research that explains the causal relationship and performs hypothesis testing using the multiple regression analysis approach. The results showed 1) Principal leadership has a positive and significant effect on the performance of SMP Negeri Se Paguyaman District, Boalemo Regency with a contribution of 25%. This means that the better the leadership of the principal, the higher the performance of SMP Negeri Se Paguyaman District, Boalemo Regency; 2) Achievement motivation has a positive and significant effect on the performance of SMP Negeri Se Paguyaman District, Boalemo Regency with a contribution of 33%. This means that the higher the achievement motivation of the teacher, the higher the performance of SMP Negeri Se Paguyaman District, Boalemo Regency; 3) Simultaneously, the principal's leadership and teacher achievement motivation have a positive and significant effect on the performance of teachers of SMP Negeri Se Paguyaman District, Boalemo Regency with a contribution value of 79%. This means that if the leadership of the principal is implemented properly and followed by the high achievement motivation of the teacher, it will simultaneously increase the performance of SMPNegeri at Paguyaman District, Boalemo Regency.